The effects of (-)-Δ(9)-tetrahydrocannabinol on reserpine-induced hypothermia in rats - Englert, L. F. (1973)
1. An intravenous injection into rats of 1 mg/kg (-)-Δ(9)-tetrahydrocannabinol Δ(9)-THC) had no effect on rectal temperature and produced in the subcellular fractions of the brain a shift of 5-hydroxytryptamine (5-HT) from the particulate or `bound' 5-HT to the supernatant or `free' fraction, whereas the noradrenaline (NA) decreased in both fractions. 2. Pretreatment of rats by an intravenous injection of 1 mg/kg Δ(9)-THC three times a week for four weeks, prevented the hypothermia and the reduction in brain 5-HT produced by an intraperitoneal injection of 15 mg/kg reserpine given 24 h after the last Δ(9)-THC injection. 3. Pretreatment of rats by a single intravenous injection of 1 mg/kg Δ(9)-THC prevented the hypothermia and reduction in brain 5-HT produced by an intraperitoneal injection of reserpine given 1 h before. The reduction in brain NA was not prevented except at the 18 h time interval. 4. An injection of 1 mg/kg Δ(9)-THC intravenously into rats 3 h after an intraperitoneal injection of reserpine accentuated the reserpine hypothermia as well as the reduction of 5-HT but not of NA in the brain. 5. The reserpine hypothermia was not prevented by a single intravenous injection of 1 mg/kg Δ(9)-THC when cinanserin, a 5-HT inhibitor, was injected 30 min before the reserpine.